Mechanistic Model of Stress Corrosion Cracking (SCC) of Carbon Steel in Acidic Solution with Presence of H2s - Asmara, Y. P.; Juliawati, Alias; Ahmad Shahrizan, Sulaiman; Jamiluddin, Jaafar (IOP Publishing, 2013)
In oil and gas industrial environments, H2S gas is one of the corrosive species which should be a main concern in designing infrastructure made of carbon steel. Combination between the corrosive environment and stress condition will cause degradation of carbon steel increase unpredictably due to their simultaneous effects. This paper will design a model that involves electrochemical and mechanical theories to study crack growth rate under presence of H2S gas. Combination crack and corrosion propagation of carbon steel, with different hydrogen concentration has been investigated. The results indicated that high concentration of hydrogen ions showed a higher crack propagation rate. The comparison between corrosion prediction models and corrosion model developed by researchers used to verify the model accuracy showed a good agreement.